Proměny Brněnského varhanního festivalu - Kučerová, Judita (Masaryk University Press, 2020)
Title in English: Metamorphoses of the Brno Organ Festival. The presented publication brings knowledge about the cultural-historical development of the festival, dramaturgical concept, choice of artists, the character of concert instruments, etc. The first chapter contains a cross-section of the 40-year history of the festival (Judita Kučerová). The historical study is followed by 3 chapters, first including the personal memories and experiences of the contemporary dramaturg and festival organizer Hana Bartošová. The essay on the organist's mission as a concert artist was contributed by the founder of the organ festival, prof. Alena Veselá, former rector of the Janáček Academy of Performing Arts in Brno and still active concert organist. The chapter on the concert organs, which the individual music evenings are played, was prepared by P. Jan Martin Bejček, OSB. The last part of the collective monograph consists of overviews of concerts held since the first years of the festival (Hana Bartošová), then in the period when the artistic and financial patronage of the Brno Organ Festival was taken over by the Club of Moravian Composers (Marek Sedláček) and an overview of non-Brno concerts (Hana Bartošová). The text has a source nature, the authors draw on preserved written documents and interviews with witnesses and festival organizers.